Personal Armour Testing versus Small Arms Ammunition when the Test Standard Doesn’t Fit - Philip GOTTS (Problemy Mechatroniki)
Small arms ammunition which may impact personal armour and is deemed to be realistic as a threat by the user, may not always comply with armour test standards. In many cases there are good practical reasons why such realistic ammunition is not included in standards, including availability and variability. However, when using some test standards, approximate equivalents have been made between realistic ammunition and those levels available within the standards, for example, the use of 30.06 AP M2 as an alternative to 7.62 x 54R B32 API. Some weapon systems not represented within test standards, are not possible to be replaced by any test level listed in any test standard. For example the Heckler and Koch MP7 and FN P90, which are positioned in performance between handgun and rifle levels. Many armour specifiers and users will make minor modifications to levels in armour standards in order to allow the test method to be valid, but with slightly different ammunition types included within a specific level. For example NIJ 0101.06 Level III+ is often specified usually for materials-based reasons. Finally the paper will introduce how bullet surrogate projectiles may be an answer to some of the issues previously highlighted.